An Implementation of Rotating Trio Exchange (RTE) Assisted by Coup Card toward Biology Learning Outcome - Nur, Rizki Amalia; Nurhidayah, Nurhidayah (Biosfer: Jurnal Tadris Biologi, 2021)
This research aims at finding the effect of the Rotating Trio Exchange (RTE) model assisted by the couple card media on the biology learning outcomes of SMAS DDI Maros. The research method was quantitative with a quasi-experimental and non-equivalent group pretest-posttest design. The research results were obtained through hypothesis testing. The pretest value in the control and the experimental classes was 0.138, where Sig. was higher than α. Therefore, there was no significant learning outcomes difference in the pretest values in both classes. Furthermore, the obtained posttest value was 0.000, where Sig. was lower than α. Therefore, there were significant learning outcomes differences between the two classes.